Asian Americans an encyclopedia of social, cultural, economic, and political history - Zhao, Xiaojian 1953-; Park, Edward J. W. (Greenwood, 2014)
"This is the most comprehensive and up-to-date reference work on Asian Americans, comprising three volumes that address a broad range of topics on various Asian and Pacific Islander American groups from 1848 to the present day" ...From Publisher Description
Keywords: Asian Americans -- Encyclopedias